Development Of Sharia Economics Textbook For Economic Education Student Lectures In The Era Of Industrial Revolution 4.0 - Melisa Wahyu Fandyansari; Putri Vina Sefaverdiana (Perisai : Islamic Banking and Finance Journal, 2020)
The era of the industrial revolution 4.0, which is currently trending in Indonesia, has made various aspects of people's lives change more advanced and completely based on technology. Therefore, educators are required to produce students who have knowledge, soft skills, and ability in the field of adequate technology. One of the programs prepared by the Economic Education Study Program is the mastery of knowledge of Sharia economic material so that one day graduates can become compatible in various fields of work, especially banking, which is currently rife with Sharia banks. The addition of this knowledge through the development of Sharia economics textbooks conducted by the RND method from Dick and Carey. The results of the pretest-posttest test, expert validation test, small scale test, and large scale test, obtained the results that the textbooks are included in the good category and are suitable for use.